Global disparity in synergy of solar power and vegetation growth - Shi Chen; Yuhan Wang; Xi Lu; Kebin He; Jiming Hao (Environmental Research Letters)
The impacts of large-scale solar photovoltaic (PV) power on local vegetation are pivotal in the context of widespread solar deployment for net-zero goals, amid escalating land fragility and use competition. Amid debates over positive or negative effects, a global pattern analysis post the past decade’s PV surge remains absent. This study quantified vegetation changes across 626 largest global PV stations and probed influencing factors using remote sensing data. Results suggest a positive effect of PV stations on local vegetation for more than 90% of stations in barren areas and 80% of stations in grasslands. But the positive effects only exert for less than 55% stations located in deserts and croplands. PV system design, especially lower installation density, along with favorable pre-existing attributes especially low original vegetation coverage, emerge as pivotal factors potentially improving PV positive impacts. These findings offer fundamental insights into cross-sectoral synergies in renewable development and vegetation growth.